DNA Repair and Cytokines: TGF-β, IL-6, and Thrombopoietin as Different Biomarkers of Radioresistance - Centurione, Lucia; Aiello, Francesca B. (Frontiers in Oncology, 2016)
Double strand breaks (DSBs) induced by radiotherapy are highly cytotoxic lesions, leading to chromosomal aberrations and cell death. Ataxia-telangiectasia-mutated (ATM)-dependent DNA-damage response, non-homologous end joining, and homologous recombination pathways coordinately contribute to repairing DSBs in higher eukaryotes. It is known that the expression of DSB repair genes is increased in tumors, which is one of the main reasons for radioresistance. The inhibition of DSB repair pathways may be useful to increase tumor cell radiosensitivity and may target stem cell-like cancer cells, known to be the most radioresistant tumor components. Commonly overexpressed in neoplastic cells, cytokines confer radioresistance by promoting proliferation, survival, invasion, and angiogenesis. Unfortunately, tumor irradiation increases the expression of various cytokines displaying these effects, including transforming growth factor-beta and interleukin-6. Recently, the capabilities of these cytokines to support DNA repair pathways and the ATM-dependent DNA response have been demonstrated. Thrombopoietin, essential for megakaryopoiesis and very important for hematopoietic stem cell (HSC) homeostasis, has also been found to promote DNA repair in a highly selective manner. These findings reveal a novel mechanism underlying cytokine-related radioresistance, which may be clinically relevant. Therapies targeting specific cytokines may be used to improve radiosensitivity. Specific inhibitors may be chosen in consideration of different tumor microenvironments. Thrombopoietin may be useful in fending off irradiation-induced loss of HSCs.